Efficiently evaluating peat-free growing media for press pots: effects of mixture combinations - Sradnick, André; Körner, Oliver (Frontiers in Horticulture, 2025)
In the last decade, many European countries set goals for peat-free horticulture, targeting both commercial growers and home gardeners. Peat substitutes are typically mixtures of several components designed to mimic peat’s properties, such as maximum water holding capacity, bulk density, and nitrogen dynamics. This study aimed to develop a peat-free mixture for seedling production in press-pots and evaluate a new statistical method for optimizing mixing strategies. The multivariate design method links component properties to mixture performance, enabling the development of targeted zero-peat mixtures. Using the XVERT system, we combined compost, wood fiber, fermented compost fiber, and clay within specific limits, applying response surface methodology and a desirability approach to predict mix effects on seedling growth. To test the substrate mixtures, Chinese cabbage seedlings (Brassica rapa subsp. pekinensis) were grown in eleven combinations of the four components. Although none of the tested mixtures fully met all predefined target properties, the response surface methodology in combination with the desirability function allowed for the identification of mixtures that closely approached these targets under the given experimental conditions. Compost and wood fiber negatively impacted mixture quality, highlighting the limitations of these common substitutes. However, the XVERT method effectively identified these issues, demonstrating its utility for designing peat-free substrates. Restricting mixtures to the tested components failed to meet horticultural quality standards. Future efforts should explore alternative components with better physical properties while leveraging the proposed experimental design method to optimize formulations. This approach offers a promising path for developing effective peat-free substrates for professional and home gardening applications.